Identification and functional analysis of exonic SNPs in MMP2 and MMP3 genes as prognostic biomarkers for breast cancer patients - Soon-Choy Chan; Fee-Wai Chin; Sharifah Noor Akmal; Sabariah Abdul Rahman; Rozita Rosli (Molecular Genetics and Genomics, 2026)

Impact of feed pretreatments on flux decline, fouling mechanisms, and protein partitioning during cold microfiltration of skim camel milk - Mairaj Khalid; Karin Schroën; Xing Yang; Pengtao Gao; Nayef Ghasem; Akmal Nazir (International Dairy Journal, 2026)

Sustainable distributed microalgae cultivation for food production through artificial intelligence-driven photobioreactor control - Ahmad Syauqi; Akmal Ramdani; Hankwon Lim; Riezqa Andika (Bioresource Technology, 2026)

CRISPR/Cas system as a novel therapeutic strategy to combat multi-drug-resistant bacteria - Akmal Zubair; Md Abu Kawsar Prodhan Hemal; Alaeldeen Ahmed; Faisal Ahmad; Yasir Waheed; Naila Afghan (Archives of Microbiology, 2026)

Red list of the threatened vascular plants of Uzbekistan - Khabibullo Shomurodov; Giuseppe Fenu; Bekhruz Khabibullaev; Natalya Beshko; Bekhzod Adilov; Farkhod Karimov; Orzimat Turginov; Ozodbek Abduraimov; Davron Dekhkonov; Ulug'bek Kadirov; Dilmurod Makhmudjanov; Inom Juramurodov; et al. (Biological Conservation, 2026)

Correction to: Preliminary Insight into the Antifungal and Anti-melanogenic Potential of a Xanthenone-based Hit Compound: In Vitro and In Vivo Zebrafish Evaluation - Amirah Hani Ramli; PuAuthorNamejali Swain; E. H. T. Thulshan Jayathilaka; Mawalle Kankanamge Hasitha Madhawa Dias; Muhammad Syafiq Akmal Mohd Fahmi; Emilia Abdul Malek; Yaya Rukayadi; Kok Wai Lam; Yee Seng Tan; Chien Ing Yeo; Cheol-Hee Kim; Mahanama De Zoysa; et al. (Journal of Pharmaceutical Innovation, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Decoding fungal effectors: A systematic review of effector diversity, molecular mechanisms, evolutionary dynamics, and host interaction strategies - Rivaldi Pratama; Ummu Azhizah Nuraini; Nur Intan Purnamasari; Fidia Hudzaifah Akmal; Azzahra Mewa Kurnia; Arif Wibowo; Toru Iwanami; Siti Subandiyah (Physiological and Molecular Plant Pathology, 2026)

Valorization of gambir leaf residues and sago starch into functional PVA-based biofilms for sustainable bio-based products in Southeast Asia - Dieter Rahmadiawan; Akmal; Hairul Abral; Stivan Kharisma Mukti; Dian Handayani; Upik Tadzkia Khairani; Dilla Ghania Putri; Shih-Chen Shi; S.M. Sapuan; R.A. Ilyas; Thiago F Santos (Biomass and Bioenergy, 2026)

Baseline Assessment of Coral Reef Condition, Diversity and Disease Prevalence in Darvel Bay, Northeastern Borneo - Aiman Azseri; Nur Angelie Agnezara Roger; Zepri Abdul Muhaimin; Mazni Muhammad Addin; Khairul Hisham Hariz; Siti Nur Hazwani Oslan; Khodzori Fikri Akmal (Thalassas: An International Journal of Marine Sciences, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

Preliminary Insight into the Antifungal and Anti-melanogenic Potential of a Xanthenone-based Hit Compound: In Vitro and In Vivo Zebrafish Evaluation - Amirah Hani Ramli; PuAuthorNamejali Swain; E. H. T. Thulshan Jayathilaka; Mawalle Kankanamge Hasitha Madhawa Dias; Muhammad Syafiq Akmal Mohd Fahmi; Emilia Abdul Malek; Yaya Rukayadi; Kok Wai Lam; Yee Seng Tan; Chien Ing Yeo; Cheol-Hee Kim; Mahanama De Zoysa; et al. (Journal of Pharmaceutical Innovation, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

Integrated Bioinformatics and Network Analysis Identifies Key Molecular Targets and Hub Genes in Zika Virus-induced Neuroinflammation - Akmal Zubair; Muhammad Ali; Adel Qlayel Alkhedaide (Journal of Molecular Neuroscience, 2026)

Biodegradation of plastics by the phosphorus-solubilising cyanobacterium Chroococcus sp. - Dani Wijaya; Japareng Lalung; Syahidah Akmal Muhammad; Peter Convey; Jebrel Abdeljawad Rashd; Law Heng Chuan; Andi Kurniawan; Nurul Huda (Journal of Applied Phycology, 2026)
Plastics often contain additives such as flame retardants, plasticisers, and stabilisers, with phosphorus-based compounds playing a key role in microbial interactions. Most previous studies have focused on heterotrophic microbes targeting carbon backbones, but their degradation efficiency remains limited. This study examined the phosphorus-solubilising ability of autotrophic cyanobacteria carrying the phoD gene to weaken polypropylene (PP) and polyethylene terephthalate (PET). Plastic samples collected from the Aquatic Research Complex fishpond at Universiti Sains Malaysia were incubated with isolates and analysed using NBRIP medium, molybdenum blue assay, UV–Vis, FTIR, SEM, and tensile strength testing over 61 days. Of the five strains isolated, Chroococcus sp. solubilised phosphorus from both PP and PET, releasing phosphorus into the medium and reducing plastic surface phosphorus. Treated plastics exhibited surface roughness, reduced dry mass, and significant tensile strength loss. This is the first report of photosynthetic cyanobacteria promoting plastic degradation via phosphorus scavenging.

Dominance in eDNA signal of introduced fish species and potential biosecurity concern in Lake Toba, Indonesia - Agung Setia Batubara; Muliari Muliari; Binari Manurung; Khairiza Lubis; Firman M. Nur; Afrizal Bigman Silitonga; Yusrizal Akmal; Mustaqim Mustaqim; Siti Maulizar; Irfannur Irfannur (Ecohydrology & Hydrobiology, 2026)

Corrigendum to “Tip loaded cyclodextrin-carvedilol complexes microarray patches” [Carbohydrate Polymers Volume 320, 15 November 2023, 121194] - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Khuriah Abdul Hamid; Natalia Moreno-Castellanos; Huanhuan Li; Ryan F. Donnelly (Carbohydrate Polymers, 2026)

From Amazonia to the World: Biology, Cultivation, and Conservation of Cardinal Tetra ( Paracheirodon axelrodi ) - Jindřich Novák; André Lincoln Barroso Magalhães; Jean Ricardo Simões Vitule; Danilo G. R. Castanho; Daniel Frynta; Michael F. Tlusty; Daniela Nováková; Kardelen Kardan; Dieter Hohl; Surya Gentha Akmal; Karel Zahrádka; Mariah Doreen Millington; et al. (Reviews in Fisheries Science & Aquaculture, 2026)

Rice husk ash-derived biosilica as a biogeochemical regulator for ameliorating acid sulfate soils in shrimp (Litopenaeus vannamei) nursery systems - Tarunamulia Tarunamulia; Mudian Paena; Akmal Akmal; Kamariah Kamariah; Akhmad Mustafa; Mohammad Syaichudin; Nur Asia Umar (Aquaculture International, 2026)

Consumer engagement towards consumption sustainability: A systematic review of willingness to pay for food waste reduction - Nazatul Akmal Nazibudin; Viola Van Onselen; Zakiyah Amini; Latifah Abd Manaf; Mohd Rusli Yacob; Nazatul Syadia Zainordin (Food and Humanity, 2026)

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Purification and Characterization of Two Neurotoxins BmKNT1 and BmKNT2 from the Scorpion Buthus martensii karsch venom - Yusuf Ali; Shamsiddin Fazliddinov; Ailin Hu; Naziermu Dongmulati; Han He; Zi Yang; Yanhua Gao; Ahmidin Wali; Haji Akber Aisa; Sharafitdin Mirzaakhmedov; Akmal Asrorov; Abulimiti Yili (Toxicon, 2026)

A review of spray-induced RNA interference for the control of phytopathogenic fungi: Mechanisms, biological barriers, and advanced delivery technologies - Rivaldi Pratama; Fidia Hudzaifah Akmal; Azzahra Mewa Kurnia (Pesticide Biochemistry and Physiology, 2026)

Biotechnological and nutraceutical evaluation of Boehmeria virgata root extract: Phytochemical profiling, antidiabetic bioactivity, and safety assessment - Haeria Doloking; Andi Andriani Musfar; Rahmi Fitri Lestari Jamal; Riska Yuniarti; Ainun Sakinah; Fitri Sea Febriani; Akmal Zulfi; Arif Setiawansyah; Muhammad Ikhlas Arsul; Alwiyah Nur Syarif; Muhammad Ikhwan Arsul (Biocatalysis and Agricultural Biotechnology, 2026)

Retraction Note: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2026)

A Forecasting Model for Charting Sustainable Future Potential of Squid Fisheries in Terengganu, Malaysia - Yeny Nadira Kamaruzzaman; Wan Akmal Wan Din; Abdullah Mohamad; Mimi Iryani Mat Taib; Aslina Nasir (Fisheries Management and Ecology, 2026)
The future of squid fisheries relies on comprehending landing patterns that are essential for sustainable management and long‐term vitality of marine ecosystems. Lack of comprehensive species‐specific data, environmental factors, and food availability constrains understanding of drivers of landing trends. Accurate predictions of future squid landings are essential for understanding population changes and guiding timely adjustments in quotas, regulations, and conservation efforts. We used seasonal‐trend loess (STL) and seasonal autoregressive integrated moving average (SARIMA) models to forecast squid landing trends in Terengganu, Malaysia, during 2023–2030, from observed squid landings during 1987–2022, to support sustainable fisheries management. Landings increased 8.5% from 2022 (14,643 metric tons) to 2030 (16,021.55 metric tons). Anticipated growth in landings suggested that squid fisheries were currently sustainable in Terengganu but would need ongoing proactive management, regulation, and conservation initiatives to sustain this status.

Mechanistic insights and emerging applications of human metapneumovirus (HMPV) treatment: From molecular design to translational immunity - Qamar Abuhassan; Ahmed Aldulaimi; Omayma Salim Waleed; Subbulakshmi Ganesan; V. Kavitha; Laxmidhar Maharana; Renu Sharma; Rafid Jihad Albadr; Akmal Abilkasimov; Mutabar Latipova; Aseel Smerat (Folia Microbiologica, 2026)

Deciphering water scarcity footprint of auxiliary paddy irrigation via Available Water Remaining (AWARE)-LCA model for sustainable groundwater infrastructure - Naseem Akhtar; Abdulghani Essyah Musbah Swesi; Syahidah Akmal Muhammad; Muhammad Izzuddin Syakir; Raed Sameeh Raja Hussain; Pahmi Husain; Ateyah Alzahrani; Anwar Ulla Khan; Ahmad Alghamdi (Environmental Monitoring and Assessment, 2026)

Validated DLLME-LC-MS/MS for rapid determination of aflatoxins in commercial seasoning powders - Sofiyatul Akmal Salim; Mohd Nazri Ismail (Food Chemistry, 2026)

Characterization of aquifer hydraulics and pumping well yield for supplemental paddy crop irrigation using pumping tests in Perak, Malaysia - Naseem Akhtar; Muhammad Izzuddin Syakir; Syahidah Akmal Muhammad; Aznan Fazli Ismail; Mohamad Shaiful Md. Yusuff; Leila Bouida; Hamza Mohamed Flafel; Pahmi Husain; Mohammed Benaafi; Taskin Ahmed; Mohammad Muqtada Ali Khan (Paddy and Water Environment, 2026)

Ecological Niche Overlap and Environmental Associations Among Species of the Morchella (Morchellaceae, Pezizomycotina) From P.R. China - Akmal Muhammad; Yinglian Deng; Syed Amir Manzoor; Changlin (Charlie) Zhao (New Zealand Journal of Botany, 2026)
Morchella species, economically significant edible fungi, are affected by numerous environmental factors; however, details concerning their ecological niche are poorly understood. Consequently, this study aims to fill this deficiency by applying a modeling approach to the fundamental niche of the Morchella genus, incorporating species from the elata and esculenta clades. In this work, we examined the distribution patterns of Morchella species in relation to significant environmental factors. The MaxEnt algorithm was utilized to conclude habitat validity. The environmental variables incorporated into the final models comprised isothermality, temperature seasonality, maximum temperature of the warmest month, mean temperature of the warmest quarter, precipitation of the wettest month, precipitation seasonality, slope, and aspect. The PCA‐env analysis revealed that the first two axes accounted for 69.55% of the overall variation in climatic conditions across the ranges of the two clades (PC1 = 41.36% and PC2 = 28.19%). An analysis and comparison of the climatic space engaged by the two primary clades, along with their overlap, were conducted. These findings emphasized the utility of ecological niche modeling for understanding how climatic conditions can influence the dispersal of Morchella clades. These results aid in formulating enhanced conservation strategies and in informed decision‐making across different ecosystems. It is essential to adopt a holistic approach to ecological modeling to foster sustainable conservation, evaluate diversity, and manage the valuable Morchella resources.

Heavy metal contamination in sediments of the Sematan-Serayan River, Sarawak: Assessment of pollution indices and environmental risk implications - Farah Akmal Idrus; Valerie Urai Ding (Environmental Monitoring and Assessment, 2026)
Sediments in river systems act as both sinks and sources of pollutants, which can have significant environmental and health implications. This study aimed to assess the concentrations of heavy metals in relation to total organic carbon (TOC) in the sediments of the Sematan-Serayan River, Sarawak, Malaysia. Sediment samples were collected in November 2024. Heavy metal and TOC concentrations were analysed via flame atomic absorption spectroscopy and a TOC analyser, respectively. The average heavy metal concentrations decreased in the order of Fe > Al > As > Zn > Ni > Cr > Pb > Mn > Cu > Co > Cd. Higher heavy metal concentrations associated with TOC were observed, particularly at stations close to anthropogenic activities, indicating pollution hotspots. The surface sediments were dominated by sand (> 90%). Pollution indices, including the contamination factor (CF), geoaccumulation index (Igeo), pollution load index (PLI), and potential ecological risk index (RI), were used to assess the severity of environmental pollution. All the stations were highly contaminated (CF > 6) and moderately to strongly polluted by Pb and As (Igeo > 2). Moreover, Stations 1 and 3–7 were considered deteriorated zones during the monsoon season (PLI > 1). The RI was very high (RI > 600) for Pb, As, Cu, Zn, and Cr at all stations. A comparison of the pollution indices with hierarchical cluster analysis suggested that anthropogenic activities were the main sources of heavy metal contamination in this river, potentially disturbing the biological functions of the benthos.

Complementary effects of polyphenolic nutraceuticals in enhancing antioxidant defense and immunity of Labeo rohita - Ozdan Akram Ghareeb; Dibakar Roy; Noman Nazeer; Mosawer Abbas; Mukhayya Ruzieva; Intizor Avazmetova; Akmal Abilkasimov; Rano Dadabaeva; Devendra Pratap Rao (Aquaculture International, 2026)

Visible-light-driven Z-scheme Cs2TiBr6–CaIn2S4 nanocomposites: Interfacial charge transfer, band alignment, and dual photocatalytic activity toward CO2 conversion and degradation of PFAS compounds - Jiabao Yang; Weigang Pan; Tian Chen; Haopeng Feng; Yinfeng Yan; Yanhong Tu; Weidong Li; Shatha A. Aldaghfag; Akmal Abilkasimov; Reda A. Haggam (Journal of Environmental Chemical Engineering, 2026)

The role of rapid molecular diagnostics in managing bloodstream infections: a microbiological insight - Jitendra Gupta; Ibrahim Saeed Gataa; Narinderjit Singh Sawaran Singh; G. PadmaPriya; Subhashree Ray; Amrita Pal; Vimal Arora; Aseel Smerat; Akmal Abilkasimov; Mutabar Latipova (Folia Microbiologica, 2026)

Solvent-selective extraction of Syzygium polyanthum bioactives for tailored polyvinyl alcohol composites: A lignocellulose-derived approach toward biorefinery-based functional materials - Dieter Rahmadiawan; Akmal; Hairul Abral; Muhammad Adlan Azka; S.M. Sapuan; Kadriadi; Dian Handayani; Dilla Ghania Putri; Upik Tadzkia Khairani; Ahmad Zikri; Shih-Chen Shi (Biomass and Bioenergy, 2026)

A mechanistic insight of neuro-inflammation signaling pathways and implication in neurodegenerative disorders - Amina Shafi; Mariam Akmal; Aisha Sethi; Zunera Chauhdary (Inflammopharmacology, 2026)

Nanotechnology-based shikonin delivery strategies for modulating the tumor immune microenvironment efficacy - Dipika Ramdas Kalambhe; Akmal M. Asrorov; Nurkhodja Mukhammedov; Yongzhuo Huang; Aihua Wu; Pengfei Zhao (Drug Delivery and Translational Research, 2026)

Unravelling the Mechanistic Role of Soil Microbial Interactions in the Suppression of Phytopathogens in Vegetable Agroecosystems of Pakistan - Basit Khan; Nadeem Ullah; Haris Maqbool; Faria Khan; Izhar Khan; Afnan Khalid; Maryam Arshad; Najeeba Parre Paker; Iffat Naz; Muhammad Akmal; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Current Microbiology, 2026)

Unlocking the role of transcription activator-like effector nuclease (TALENs) and zinc finger nuclease (ZFN) in the treatment of HIV - Akmal Zubair; Muhammad Ali; Faisal Ahmad; Saed Ayidh Althobaiti (Molecular Biology Reports, 2025)

Mechanisms of S-phase arrest and mitochondrial dysfunction in complex III by DHODH inhibitors in tumorigenic TNBC cells - Muhammad Aiman Akmal Shahhiran; Mohamad Fairus Abdul Kadir; Nurshamimi Nor Rashid; Puteri Shafinaz Abdul-Rahman; Shatrah Othman (Histochemistry and Cell Biology, 2025)

Protein networks: integrating pathways for plant heat stress adaptation - Akmal Zubair; Sania Zaib; Malaika; Karishma; Manal S. Ebaid (Functional & Integrative Genomics, 2025)

New hope and promise with CRISPR-Cas9 technology for the treatment of HIV - Hesham M. Hassan; Akmal Zubair; Mohamed H. Helal; Wesam Taher Almagharbeh; Ranya Mohammed Elmagzoub (Functional & Integrative Genomics, 2025)

Comprehensive review of bioactive compounds from microalgae as promising source for industrial applications - Siti Nur Hazwani Oslan; Ng Jia Xuan; Fikri Akmal Khodzori; Bibi Nabihah Abdul Hakim; Nurul Huda; Norliza Julmohamad; Noora Barzkar (Algal Research, 2025)

Characterisation of flavonoids from methanolic extract of Brucea javanica leaves using feature-based molecular networking, SIRIUS5, and NMR spectroscopy - Anis Irfan Norazhar; Nurulfazlina Edayah Rasol; Nor Syaidatul Akmal Mohd Yousof; Nor Hadiani Ismail; Syahrul Imran (Natural Product Research, 2025)

Spectroscopic Studies of the Interaction of some Monomer and Homodimer Styrylcyanine Dyes with DNA - Akmal Sh. Yarmukhamedov; Eldar N. Kurtaliev; Ilzar Khairov; Negmat Nizomov (Journal of Fluorescence, 2025)

The nexus of agricultural land use change and food security: A comprehensive systematic review - Freshteh Avatefi Akmal; Yaser Mohammadi (Land Use Policy, 2025)

Alantolactone: structural enhancements and therapeutic insights for cancer and inflammation - Muzaffar Kayumov; Fotima A. Sobirova; Okhunjon Khasanov; Nurkhodja Mukhamedov; Akmal M. Asrorov; Sharafitdin Mirzaakhmedov (Natural Product Research, 2025)

Low-temperature on-board hydrogen production using a novel hollow fibre-based packed bed reactor - Claire Leishman; Yuxiang Liu; Muhammad Akmal Bin Mohd Faisal; Kang Li; Francisco R. García-García (Chemical Engineering Journal, 2025)

Physics-Based Discrepancy Modeling for Well Log Imputation - Laaiba Akmal; Michael J. Pyrcz (Mathematical Geosciences, 2025)
Evaluating subsurface formations through wireline logs is critical for petrophysical analysis in exploration activities yet is often hindered by data quality issues and measurement errors. Addressing these challenges, we propose a novel formation evaluation discrepancy modeling workflow that synergizes machine learning with physics-based models for enhanced well log imputation and interpretation. The workflow is demonstrated on a synthetic dataset that includes standard well logs (e.g., porosity, resistivity, saturation) and facies classifications, generated to represent a geologically realistic environment of alternating marine shales and fluvial or deltaic sandstones. Our methodology leverages physics-based predictions from established principles, such as Gassmann’s equations and Athy’s law, to ensure adherence to known physical laws. We then conduct discrepancy analysis against actual observations to guide feature selection, integrating mutual information and random forest importance ranking. By applying machine learning to predict these discrepancies and combining these predictions on top of our physics-based predictions, a form of machine learning boosting, we refined the initial estimates and significantly improved accuracy. Depth and facies emerge as key predictors in our feature importance analysis, with our discrepancy models combining an initial physics model and random forest model significantly improving prediction accuracy (mean squared error [MSE] of 7.66) over only physics-based predictions (MSE of 18,413). Moreover, Shapley analysis offers additional insights, elucidating the complex influences of model features on predictions and learning the missing physics from the machine learning-based model of discrepancy. Our proposed physics-based discrepancy modeling for well log imputation combines theoretical physics and data-driven predictions to provide more accurate, actionable insights to support reservoir exploration and development decisions.

Advancements in clay mineral adsorbents of montmorillonite and kaolinite for effective water contamination remediation - H. Heryanto; D. Tahir; A. Akmal; V. Setiawan (International Journal of Environmental Science and Technology, 2025)

Utilization of duckweed in phytomining of gold mine tailing and its potential to produce gold nanoparticle - Rizki Maulana Yusuf; Muhammad Alhas Finaldin; Wahyuni Eka Putri; Aurora Karina Chandra; Akmal Jihad; Yuliati Herbani; Awalina Satya; Evi Susanti; Hamim Hamim (Environmental Science and Pollution Research, 2025)

Preparation of a novel reusable 2D-MXene with flower-like LDH composite for ultra-high adsorption of congo red and doxycycline: Stability and environmental application - Ismail Marouani; Waqed H. Hassan; Narinderjit Singh Sawaran Singh; Mudassir Hasan; Alisher Abduvokhidov; Mukhtorjon Karimov; Akmal Abilkasimov; Ibrahm Mahariq; M.A. Diab (Journal of Water Process Engineering, 2025)

Preliminary study on influence of UV radiation on the light transmittance of light-transmitting concrete - Shing Mei Chiew; Izni Syahrizal Ibrahim; Anika Zafiah M. Rus; M. Amirulhusni M. Fadzir; M. Akmal Abd Rabbi (Journal of Cleaner Production, 2025)

OhmNet: Advanced neural network-based viscosity prediction of sauces for efficient Ohmic heating processing - Tasmiyah Javed; Muhammad Akmal; Timofei Breikin; Caroline Millman; Hongwei Zhang (Innovative Food Science & Emerging Technologies, 2025)

Green synthesis of durian shell-derived activated carbon with enhanced carboxylic functionalization and graphitization via gamma irradiation in ethanol and ethylene glycol for supercapacitor applications - Phonpimon Numee; Tanagorn Sangtawesin; Akmal Hadi Ma'Radzi; Kotchaphan Kanjana (Biomass and Bioenergy, 2025)

Novel sequential ozonolysis-hydrolysis treatments for microcrystalline cellulose synthesis from oil palm empty fruit bunch - Pavitra Thevi Arnandan; Wan Nor Nadyaini Wan Omar; Zhahidah Husna Hassan; Muhammad Sufri Abd Muhaimin; Danish Akmal Jihat@Ahmad; Makam Mba Michele Raissa; Amnani Shamjuddin; Ken-Lin Chang; Nor Aishah Saidina Amin (Biomass and Bioenergy, 2025)

Relationship between perceived maneuverability and compensatory eye movements under systematically varied time constants of ride-on machinery - Muhammad Akmal Mohammed Zaffir; Daisuke Sakai; Yuki Sato; Takahiro Wada (Experimental Brain Research, 2025)

Fundamentals of electrocatalysis and photocatalysis for the remediation of wastewater containing methylene blue - Andi Akmal; Dahlang Tahir; Heryanto Heryanto; Muh Ade Artasasta; Bulkis Musa (Environmental Science and Pollution Research, 2025)

Resistance development, cross-resistance, and inheritance patterns in clothianidin and triazophos resistant strains of Oxycarenus hyalinipennis - Rabia Saeed; Naeem Abbas; Muhammad Akmal; Jam Nazir Ahmad (Crop Protection, 2025)

Evaluation of physical and chemical modifications to drug reservoirs for stimuli-responsive microneedles - Luchi Li; Qonita Kurnia Anjani; Aaron R. J. Hutton; Mingshan Li; Akmal Hidayat Bin Sabri; Lalitkumar Vora; Yara A. Naser; Yushi Tao; Helen O. McCarthy; Ryan F. Donnelly (Drug Delivery and Translational Research, 2025)
Hydrogel-forming microneedle (MN) arrays are minimally-invasive devices that can penetrate the stratum corneum , the main barrier to topical drug application, without causing pain. However, drug delivery using hydrogel-forming MN arrays tends to be relatively slow compared to rapid drug delivery using conventional needles and syringes. Therefore, in this work, for the first time, different physical and chemical delivery enhancement methods were employed in combination with PVA-based hydrogel-forming MN arrays. Using a model drug, ibuprofen (IBU) sodium, the designed systems were assessed in terms of the extent of transdermal delivery. Iontophoresis (ITP) and heat-assisted drug delivery technology were investigated as physical permeation enhancement techniques. Ex vivo studies demonstrated that the ITP (0.5 mA/cm 2 )-mediated combination strategy significantly enhanced the transdermal permeation of IBU sodium over the first 6 h (~ 5.11 mg) when compared to MN alone (~ 1.63 mg) ( p < 0.05). In contrast, heat-assisted technology showed almost no promoting effect on transdermal delivery. Furthermore, IBU sodium-containing rapidly dissolving lyophilised and effervescent reservoirs, classified as chemical modification methods, were prepared. Both strategies achieved rapid and effective ex vivo IBU sodium permeation, equating to ~ 78% (30.66 mg) and ~ 71% (28.43 mg) from lyophilised and effervescent reservoirs, respectively. Moreover, in vivo pharmacokinetic studies showed that the IBU sodium plasma concentration within lyophilised and effervescent groups reached a maximum concentration (C max ) at 4 h (~ 282.15 µg/mL) and 6 h (~ 140.81 µg/mL), respectively. These strategies not only provided rapid achievement of therapeutic levels (10–15 µg/ml), but also resulted in sustained release of IBU sodium for at least 48 h, which could effectively reduce the frequency of administration, thereby improving patient compliance and reducing side effects of IBU sodium. Graphical Abstract

Advances in Antibiotic Biodegradation: Emerging Strategies and Challenges in Mitigating Environmental Contamination and Resistance - Ibnu Maulana Hidayatullah; Soen Steven; Adi Kusmayadi; Iftita Rahmatika; Muhammad Reski; Ramaraj Boopathy; Muhamad Akmal Alfatan; Putri Wilhelmina Gusanti Purba (Current Pollution Reports, 2025)

A novel active packaging film based on polyvinyl alcohol/bajakah tampala (Spatholobus littoralis hassk) extract: Enhancing mechanical, UV protection, thermal stability, antimicrobial, and barrier properties - Kadriadi; Dieter Rahmadiawan; Hairul Abral; Ilhamdi; Muhammad Ivan; Akmal; Dian Handayani; Laila Rezki Septria Ningrum; Rahmi Syarifah Masri; Bernadeta Ayu Widyaningrum; Mohamad Haafiz Mohamad Kassim; Melbi Mahardika (Food Bioscience, 2025)

High-efficiency biochar production from oil palm fronds using acidic pretreatment and co-torrefaction with waste cooking oil - Anisa Mutamima; Sunarno Sunarno; Indra Purnama; Nurfatihayati Nurfatihayati; Akmal Novendri; Rinalsi Anesta; Rozanna Sri Irianty (Waste Disposal & Sustainable Energy, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

The Jekyll and Hyde fish: Phenotype as a determinant of the invasion potential of Polypterus senegalus Cuvier, 1829 - Tereza Valchářová; Pavel Horký; Surya Gentha Akmal; Yonvitner; Jiří Patoka; Ondřej Slavík (Applied Animal Behaviour Science, 2025)

Morphological characteristics and phylogenetic analysis reveal Punctulariopsis fissurata sp. nov. (Punctulariaceae, Basidiomycota) from Yunnan, China - Akmal Muhammad; Minglan Chen; Wen Li; ChangLin Zhao (New Zealand Journal of Botany, 2025)
A new wood‐inhabiting fungal species, Punctulariopsis fissurata , is proposed based on morphological description and molecular verification. The species is characterised by the resupinate basidiomata with a pinkish buff salmon hymenial surface, a monomitic system with the generative hyphae bearing clamp connections and the presence of dendrohyphidia with broadly ellipsoid basidiospores measuring 13–15.5 × 8.5–11.5 µm. Phylogenetic analysis of the combined nrDNA‐ITS and LSU gene sequences verified that P. fissurata formed an independent lineage sister to P. efibulata with strong statistical support. A full description, illustrations and phylogenetic analysis results of the new species are provided.

Evaluating the performance of the wastewater treatment plant in intensive whiteleg shrimp (Litopenaeus vannamei) brackishwater pond aquaculture - Akhmad Mustafa; Rachman Syah; Mudian Paena; Tarunamulia; Wasir Samad; Erna Ratnawati; Kamariah; Admi Athirah; Ruzkiah Asaf; Akmal; Mohammad Syaichudin; Hamzah; et al. (Environmental Science and Pollution Research, 2025)

Innovative use of camel whey proteins, quercetin, and starch as ternary complexes for emulsion stabilization at the Micro and Nano scale - Waqas.N. Baba; Hina Khan; Akmal Nazir; Sajid Maqsood (Food Chemistry, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Pathology of an unusual outbreak of fatal disease associated with mycobacterial and Pseudomonas aeruginosa infections and intracytoplasmic inclusion bodies in juvenile spectacled caimans (Caiman crocodilus) - Sufiah U.N.K. Azlin; Nurul F. Muhammad Husairy; Charisha Fraser; Nurul I.U. Zahli; Mohd N. Akmal; Annas Salleh (Journal of Comparative Pathology, 2025)

Exposure to bisphenol S induces organ toxicity by disrupting oxidative and antioxidant defense system and blood physiology in Labeo rohita (Hamilton, 1822) - Shabbir Ahmad; Hasnain Akmal; Farhat Jabeen; Khurram Shahzad (Fish Physiology and Biochemistry, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Elemental Profiling of Common Anti-diabetic Medicinal Plants of Swat and Peshawar Districts of Khyber Pakhtunkhwa (KPK) Province of Pakistan: An Investigation Using PIXE and ICP-OES - Akmal Zubair; Sania Zaib; Mingkun Zhu; Mohamed Mohany (Biological Trace Element Research, 2025)

The potential of hydrolyzed chicken feather meal as a partial replacement for fish meal and its effects on the growth and health status of African catfish (Clarias gariepinus) fingerlings - Nik Nur Akmal ‘Aliah Abdul Rashid; Zulhisyam Abdul Kari; Parashuram Kallem; Suniza Anis Mohamad Sukri; Syed Muhammad Al-Amsyar; Noor Khalidah Abdul Hamid; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Martina Irwan Khoo; Krishnakumar Velayudhannair; Ajay Guru (Aquaculture International, 2025)

HIV-1 Nef Gene Characterization and Subtype Analysis in Pakistan: A Molecular Docking Approach with Mastoparan-L Peptide - Akmal Zubair; Muhammad Ali; Naseem Akhtar (International Journal of Peptide Research and Therapeutics, 2025)

Revisiting the History of Ornamental Aquaculture in Europe to Understand the Benefits and Drawbacks of Freshwater Fish Imports - Jindřich Novák; Dieter Hohl; Martin Stuchlík; Jaroslav Hofmann; Michael F. Tlusty; André Lincoln Barroso Magalhães; Alberto Maceda‐Veiga; Surya Gentha Akmal; Gen Hua Yue; Pradeep Kumkar; Sean M. Marr; Joseph R. Sara; et al. (Reviews in Aquaculture, 2025)
Ornamental aquaculture and fishkeeping are very popular with millions of enthusiasts worldwide. The number of newly imported fish species for ornamental purposes grew slowly from World War I until the 1980s. It then exponentially increased until now with more than 7900 species and a large number of scientifically undescribed morphotypes. Here we present the first comprehensive review of freshwater and brackish fish importations during the boom of ornamental fish keeping at the turn of the Millennium and discuss this with a cultural and socio‐economic lens in the European context. The increase in imports accelerated following the availability of air transport and the end of the Cold War. From the list of traded species, the largest number of species imported for ornamental purposes was found in the following groups: armored loricariid catfish (family Loricariidae), cory catfish (family Callichthyidae, subfamily Callichthyinae), cichlids of African Great Lakes (order Cichliformes), killifish (egg‐laying species of the order Cyprinodontiformes), and characids (order Characiformes). These taxa represent ca. 74% of all fresh and brackish water ornamental fish species. The species of fish with the ability to absorb atmospheric oxygen (e.g., Belontidae, including gouramis and bettas) have dominated the market, but their ratio to the other species has declined during the modern era of ornamental aquaculture (after the end of WWI). By identifying the most popular aquarium species traded through the history of the aquarium trade, our findings aim to guide present‐day management of ornamental aquaculture and better inform invasion risk assessments.

Citric acid plays a dual ‘synergistic/antagonistic’ role with antibiotics in multidrug-resistant Salmonella Typhimurium - Bismi Phasaludeen; Dania Mustafa Darwich; Greeshma Bharathan; Jennifer Osamede Airouyuwa; Sajid Maqsood; Akmal Nazir; Shabarinath Srikumar (Food Bioscience, 2025)

PolarBytes: Advancing polar research with a centralized open-source data sharing platform - Nur Haznirah Hazman; Rohaizaazira Mohd Zawawi; Ainin Sofia Jusoh; Muhammad Akmal Remli; Marieanne Christie Leong; Mohd Saberi Mohamad; Sarahani Harun (Environmental Modelling & Software, 2025)

Highly efficient iodine capture and selective adsorption and removal of cationic dyes by using a copper-based coordination polymer decorated over graphene oxide and carbon nanotubes - Khalil M.A. Qasem; Mohammad Yasir Khan; Shaikh Arfa Akmal; Hatem A.M. Saleh; Mohd Mehtab; M. Shahid; Mansour A.S. Salem; Mohammad Mujahid Ali Khan; Younes S.A. Ghanem; Abdul Malik; Abdul Moheman (Journal of Water Process Engineering, 2025)

Role model of environmental governance to support the development of high-tech whiteleg shrimp ponds (Litopenaeus vannamei) - Mudian Paena; Akhmad Mustafa; Tarunamulia; Imam Taukhid; Erna Ratnawati; Ruzkia Asaf; Admi Athirah; Kamariah; Akmal; Mohammad Syaichudin; Hamzah (Aquaculture International, 2025)

Performance and land characteristics of brackishwater pond to support sustainability of Pacific white shrimp (Litopenaeus vannamei) culture intensive technology - Akhmad Mustafa; Rachman Syah; Tarunamulia; Mudian Paena; Wasir Samad; Erna Ratnawati; Admi Athirah; Ruzkiah Asaf; Akmal; Kamariah; Zylshal; Sarip Hidayat; et al. (Environmental Science and Pollution Research, 2024)

Carboxymethyl cellulose – Polyvinyl alcohol bioactive films loaded with green extracted date seed polyphenols for active packaging of Shiitake mushrooms - Kehinde Ganiyat Lawal; Raouf Aslam; Akmal Nazir; Balan Sundarakani; Constantinos Stathopoulos; Sajid Maqsood (Food Bioscience, 2024)

A Pragmatic Approach to Fetal Monitoring via Cardiotocography Using Feature Elimination and Hyperparameter Optimization - Fırat Hardalaç; Haad Akmal; Kubilay Ayturan; U. Rajendra Acharya; Ru-San Tan (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Production and analysis of synthesized bacterial cellulose by Enterococcus faecalis strain AEF using Phoenix dactylifera and Musa acuminata fruit extracts - Ashraf Sami Hassan AL-Hasabe; Ahmad Faizal Bin Abdull Razis; Nadiya Akmal Binti Baharum; Choo Yee Yu; Nurulfiza Binti Mat Isa (World Journal of Microbiology and Biotechnology, 2024)

Production and characterization of bacterial cellulose synthesized by Enterobacter chuandaensis strain AEC using Phoenix dactylifera and Musa acuminata - Ashraf Sami Hassan AL-Hasabe; Ahmad Faizal Bin Abdull Razis; Nadiya Akmal Binti Baharum; Choo Yee Yu; Nurulfiza Mat Isa (Archives of Microbiology, 2024)

Identification of the myxobacterial secondary metabolites Aurachin A and Soraphinol A as promising inhibitors of thymidylate kinase of the Monkeypox virus - Yasir Ali; Azmat Ali Khan; Amer M. Alanazi; Sidikov Akmal Abdikakharovich; Junaid Ali Shah; Zhi-Guang Ren; Saadullah Khattak (Molecular Diversity, 2024)

Clinical trials and recent progress in HIV vaccine development - Akmal Zubair; Bushra Bibi; Faiza Habib; Arooba Sujan; Muhammad Ali (Functional & Integrative Genomics, 2024)

The Interaction Of Homodimer Styrylcyanine Dyes With Sodium Dodecyl Sulfate And Triton X-100 - Eldar N. Kurtaliev; Akmal Sh. Yarmukhamedov; Asalya A. Djamalova; Negmat Nizomov; Sergei N. Terekhov (Journal of Fluorescence, 2024)

Remediation of benzo[α]pyrene contaminated soil using iron naturally bearing in tropical soil: A new frontier in catalyst-free in soil remediation - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Chemosphere, 2024)

P19-45 Data management for image-based characterisation of 2D nano-materials - P.P. Ankli; A. Ali; S. Hodzic; A. Logachov; K. Maciejczuk; A. Milochiv; S. Hardy; B. Hardy; S. Novak; E. Kranjc; V. Kononenko; S. Saje; et al. (Toxicology Letters, 2024)

Soil remediation and nano-biosilica: a potential combination to improve the environmental quality of brackishwater aquaculture ponds affected by acid sulfate soils - Tarunamulia Tarunamulia; Akhmad Mustafa; Mudian Paena; Akmal Akmal; Mohammad Syachuddin; Kamariah Kamariah; Erna Ratnawati; Muhammad Ilman (Environmental Science and Pollution Research, 2024)

The potential of carboxylmethyl cellulose from empty fruit bunch as versatile material in food coating: A review - Raissa Michele Mba Makam; Wan Nor Nadyaini Wan Omar; Danish Akmal bin Jihat @. Ahmad; Nur Umisyuhada Mohd Nor; Amnani Shamjuddin; Nor Aishah Saidina Amin (Carbohydrate Polymers, 2024)

Biotechnological approaches in the production of plant secondary metabolites for treating human viral diseases: Prospects and challenges - Mohtaram Mahmoudieh; Mohammad Reza Naghavi; Zulfazli M. Sobri; Azzreena Mohamad Azzeme; Nazrin Abd-Aziz; Nik Mohd Afizan Nik Abd Rahman; Noorjahan Banu Alitheen; Yazmin Hussin; Ghazaleh Bahmanrokh; Nadiya Akmal Baharum (Biocatalysis and Agricultural Biotechnology, 2024)

Physicochemical, functional, and nutraceutical properties of Spirulina and Chlorella biomass: A comparative study - Yakoub Ladjal-Ettoumi; Meriem Hamadi; Lina Hadjer Douik; Zakaria Cherifi; Akmal Nazir (Algal Research, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

Harnessing digital innovations for climate action and market access: Opportunities and constraints in the CWANA region - Martin Paul Jr. Tabe-Ojong; Yousra Salama; Kibrom A. Abay; Fatma Abdelaziz; Claudia Zaccari; Akmal Akramkhanov; Gianpiero Menza; Oyture Anarbekov (Global Food Security, 2024)

Determination of aflatoxins in rice from Penang, Malaysia by dispersive liquid–liquid micro-extraction and LC–MS/MS - Sofiyatul Akmal Salim; Nur Harniada Baharudin; Nur Shahila Ibrahim; Zalilawati Abd Ghani; Mohd Nazri Ismail (Food Additives & Contaminants: Part A, 2024)

Advanced oxidation of polycyclic aromatic hydrocarbons in tropical soil: Self-catalytic utilization of natural iron contents in an oxygenation reactor supported with persulfate - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Masoom Raza Siddiqui; Mahboob Alam (Science of The Total Environment, 2024)

Simultaneous determination of picomolar level of dissolved silver with other key trace metals in seawater samples using solid phase extraction and isotope dilution methods - Kuo Hong Wong; Keisuke Nishitani; Hajime Obata; Hideki Fukuda; Hiroshi Ogawa; Farah Akmal Idrus; Fatimah A'tirah binti Mohamad; Asami S. Mashio; Hiroshi Hasegawa (Marine Chemistry, 2024)

Pollutant levels in the waters of the industrial area of North Aceh and Lhokseumawe Regency, Indonesia - Muliari Muliari; Mahdaliana; Irfannur Irfannur; Yusrizal Akmal; Agung Setia Batubara (Marine Pollution Bulletin, 2024)

Energy and social factor decomposition to identify drivers impeding sustainable environmental transition in emerging countries: SDGs-2030 progress assessment using LMDI analysis - Qi Gao; Nida Raza; Dandan Sun; Muhammad Akmal; Faiz Nayab (Environmental Science and Pollution Research, 2024)

Harnessing the power of bacterial laccases for xenobiotic degradation in water: A 10-year overview - Mujeeb ur Rahman; Muhammad Wajid Ullah; Junaid Ali Shah; Sivasamy Sethupathy; Hazart Bilal; Sidikov Akmal Abdikakharovich; Afaq Ullah Khan; Khalid Ali Khan; Noureddine Elboughdiri; Daochen Zhu (Science of The Total Environment, 2024)

Tropical soil remediation from pyrene: Release the power of natural iron content in soil for the efficient oxidant's activation - Mohammad Qutob; Mohd Rafatullah; Syahidah Akmal Muhammad; Khalid A. Alamry; Mahmoud A. Hussein (Journal of Environmental Management, 2024)

MAP-box: a novel, low-cost and easy-to-fabricate 3D-printed box for the storage and transportation of dissolving microneedle array patches - Qonita Kurnia Anjani; Álvaro Cárcamo-Martínez; Luki Ahmadi Hari Wardoyo; Natalia Moreno-Castellanos; Akmal Hidayat Bin Sabri; Eneko Larrañeta; Ryan F. Donnelly (Drug Delivery and Translational Research, 2024)
Research on the use of microarray patches (MAPs) has progressed at an unprecedented rate over the years, leading to the development of many novel drug delivery systems. As the technology approaches patients, there are several key aspects that ought to be addressed in order to facilitate the smooth translation of MAPs from bench to bedside. One integral factor includes the choice of devices and packaging for the storage of MAPs. In the current work, a slide-and-seal box, MAP-box, was developed for the storage of dissolving MAPs, using fused-deposition modelling. The device has been designed to act as a pill-box for MAPs not only to provide protection for MAPs from the environment, but also to improve patient’s adherence to treatment. The overall design of the MAP-box was simple, yet offers the capability of sealing and protecting dissolving MAPs up to 30 days. Donepezil HCl was formulated into a dissolvable MAP, which was used to treat dementia related to Alzheimer’s disease. This compound was used as a model formulation to evaluate the utility of the 3D printed MAP-box when placed under three storage conditions: 5 °C and ambient humidity, 25 °C and 65% relative humidity and 40 °C and 75% relative humidity. It was shown that the slide-and-seal box was able to confer protection to MAPs for up to 30 days under accelerated stability study conditions as the drug loading, mechanical properties and insertion properties of MAPs remained unaffected when compared to the unpackaged MAPs stored under these same parameters. These preliminary data provide evidence that the MAP-box prototype may be of great utility for the storage of single or multiple MAPs. Nevertheless, future work will be needed to evaluate their patient usability and its application to different types of MAP systems to fully validate the overall robustness of the prototype. Graphical Abstract

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Tip loaded cyclodextrin-carvedilol complexes microarray patches - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Khuriah Abdul Hamid; Natalia Moreno-Castellanos; Huanhuan Li; Ryan F. Donnelly (Carbohydrate Polymers, 2023)

Assessing Household’s Municipal Waste Segregation Intentions in Metropolitan Cities of Pakistan: A Structural Equation Modeling Approach - Tanzila Akmal; Faisal Jamil; Muhammad Haseeb Raza; Cosimo Magazzino; Babar Hussain (Environmental Monitoring and Assessment, 2023)
There is a growing concern about inappropriate waste disposal and its negative impact on human health and the environment. The objective of this study is to understand household waste segregation intention considering psychological, institutional, and situational factors simultaneously. Insights into the motivations of household waste segregation drivers may assist in a better knowledge of how to pursue the most efficient and effective initiatives. For this purpose, data from a representative sample comprising 849 households is obtained from the twin cities of Islamabad and Rawalpindi (Pakistan). The empirical analysis employs a Structural Equation Modeling (SEM) approach, showing that policy instruments have significant direct and indirect impacts on households’ segregation intentions. The results highlight that government policy instruments strengthen personal and perceived norms for waste segregation intentions, resulting in an external intervention that would encourage intrinsic motivation. Therefore, policy actions become the main entry point for initiating waste segregation behavior. Public policy must continue to emphasize waste segregation since it may help resource recovery. This is imperative because the environment is a shared resource, and its conservation increases social welfare.

A comprehensive description of the exoskeleton of six Lobster species (Genus Panulirus) in Aceh Province, Indonesia - Yusrizal Akmal; Irfannur Irfannur; Muliari Muliari; Agung Setia Batubara; Muchammad Yunus; Hani Plumeriastuti; Yeni Dhamayanti (Fisheries Research, 2023)

Evaluation of radon hazards at the rural settlements of Uzbekistan - Akmal Safarov; Askar Safarov; Shakhboz Khasanov; Eldor Umirzakov; Ram Proshad; Sitora Suvanova; Maruf Muminov (Environmental Monitoring and Assessment, 2023)

Resistance and genomic characterization of a plasmid pkh2101 harbouring erm (B) isolated from emerging fish pathogen Lactococcus garvieae serotype II in Japan - Muhammad Akmal; Mami Akatsuka; Issei Nishiki; Terutoyo Yoshida (Journal of Fish Diseases, 2023)
The emergence of antibiotic‐resistant pathogenic strains of Lactococcus garvieae serotype II isolated from fish in Japan has become a growing concern in recent years. The data on drug susceptibility and its associated resistance mechanism are limited. Therefore, the present study was conducted to determine the minimum inhibitory concentrations (MICs) of chemotherapeutic agents against 98 pathogenic strains of emerging Lactococcus garvieae serotype II isolated from fish from six different prefectures in Japan from 2018 to 2021. The tested strains were resistant to erythromycin, lincomycin and tiamulin. PCR amplification revealed the presence of erm (B) in all erythromycin‐resistant strains, while a conjugation experiment confirmed that these strains carried erm (B) that could be transferred to recipient Enterococcus faecalis OG1RF with frequencies from 10 −4 to 10 −6 per donor cells. Nucleotide sequencing of the representative isolated plasmid pkh2101 from an erythromycin‐resistant strain showed that it was a 26,850 bp molecule with an average GC content of 33.49%, comprising 31 CDSs, 13 of which remained without any functional annotation. Comparative genomic analysis suggested that pkh2101 shared the highest similarity (97.57% identity) with the plasmid pAMbeta1, which was previously isolated clinically from Enterococcus faecalis DS‐5. This study provides potential evidence that the plasmid harbouring erm (B) could be a source of antibiotic resistance transmission in emerging L. garvieae infection in aquaculture.

Evaluation of perennial reference evapotranspiration (ETo) over a typical dryland using satellite images: A case study from Uzbekistan - Umida Makhmudova; Sayidjakhon Khasanov; Akmal Karimov; Sarvar Abdurakhmonov (Ecohydrology & Hydrobiology, 2023)

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

Spatial pattern analysis on incidence of dengue hemorrhagic fever (DHF) in the Leuwigajah, West Java, Indonesia - Ummyatul Hajrah; Dzul Akmal; Asep Dian Abdillah; Fajar Nugraha (Spatial Information Research, 2023)

Wavenumber unwrapping for the automated analysis of SASW measurements - Sung-Ho Joh; Jerikah Anne Vivar; Haziq Akmal (Soil Dynamics and Earthquake Engineering, 2023)

The native range of Xenophthalmus pinnotheroides White, 1846 (Decapoda: Brachyura) predicted by climate matching with the first record for Vietnam - Jiří Patoka; Alexandr Prokin; Cu Nguyen Dinh; Alexander Tsvetkov; Surya Gentha Akmal; Miloslav Petrtýl; Martin Bláha (Biologia, 2022)

Oil palm yield prediction across blocks from multi-source data using machine learning and deep learning - Yuhao Ang; Helmi Zulhaidi Mohd Shafri; Yang Ping Lee; Shahrul Azman Bakar; Haryati Abidin; Mohd Umar Ubaydah Mohd Junaidi; Shaiful Jahari Hashim; Nik Norasma Che’Ya; Mohd Roshdi Hassan; Hwee San Lim; Rosni Abdullah; Yusri Yusup; et al. (Earth Science Informatics, 2022)

Tissue Distribution, Histopathological and Genotoxic Effects of Magnetite Nanoparticles on Ehrlich Solid Carcinoma - Heba Bassiony; Akmal A. El-Ghor; Taher A. Salaheldin; Salwa Sabet; Mona M. Mohamed (Biological Trace Element Research, 2022)
Nanoparticles can potentially cause adverse effects on cellular and molecular level. The present study aimed to investigate the histopathological changes and DNA damage effects of magnetite nanoparticles (MNPs) on female albino mice model with Ehrlich solid carcinoma (ESC). Magnetite nanoparticles coated with L-ascorbic acid (size ~ 25.0 nm) were synthesized and characterized. Mice were treated with MNPs day by day, intraperitoneally (IP), intramuscularly (IM), or intratumorally (IT). Autopsy samples were taken from the solid tumor, thigh muscle, liver, kidney, lung, spleen, and brain for assessment of iron content, histopathological examination, and genotoxicity using comet assay. The liver, spleen, lung, and heart had significantly higher iron content in groups treated IP. On the other hand, tumor, muscles, and the liver had significantly higher iron content in groups treated IT. MNPs induced a significant DNA damage in IT treated ESC. While a significant DNA damage was detected in the liver of the IP treated group, but no significant DNA damage could be detected in the brain. Histopathological findings in ESC revealed a marked tumor necrosis, 50% in group injected IT but 40% in group injected IP and 20% only in untreated tumors. Other findings include inflammatory cell infiltration, dilatation, and congestion of blood vessels of different organs of treated groups in addition to appearance of metastatic cancer cells in the liver of non-treated tumor group. MNPs could have an antitumor effect but it is recommended to be injected intratumorally to be directed to the tumor tissues and reduce its adverse effects on healthy tissues.

Complete genome sequence of a novel lytic bacteriophage, PLG-II, specific for Lactococcus garvieae serotype II strains that are pathogenic to fish - Muhammad Akmal; Issei Nishiki; Nikita Zrelovs; Terutoyo Yoshida (Archives of Virology, 2022)

In Vitro Permeation Studies on Carvedilol Containing Dissolving Microarray Patches Quantified Using a Rapid and Simple HPLC-UV Analytical Method - Qonita Kurnia Anjani; Akmal Hidayat Bin Sabri; Mary B. McGuckin; Huanhuan Li; Khuriah Abdul Hamid; Ryan F. Donnelly (AAPS PharmSciTech, 2022)
Analytical method validation is a vital element of drug formulation and delivery studies. Here, high-performance liquid chromatography in conjunction with UV detection (HPLC-UV) has been used to produce a straightforward, quick, yet sensitive analytical approach to quantify carvedilol (CAR). A C18 column was used to isolate the analyte from the mixture by isocratic elution with a mobile phase comprising a mixture of 0.1% v/v trifluoroacetic acid in water and acetonitrile in a ratio of 65:35 v/v at a flow rate of 0.6 mL min −1 . Linearity was observed for CAR concentrations within the range of 1.5–50 μg mL −1 ( R 2 = 0.999) in phosphate buffer saline and within the range of 0.2–6.2 μg mL −1 ( R 2 = 0.9999) in methanol. The International Council on Harmonization (ICH) requirements were followed throughout the validation of the isocratic approach, rendering it specific, accurate, and precise. Moreover, robustness tests indicated that the method remained selective and specific despite small deliberate changes to environmental and operational factors. An efficient extraction procedure was also developed to extract and quantify CAR from excised neonatal porcine skin, resulting in recovery rates ranging from 95 to 97%. The methods reported here have been successfully utilised to evaluate CAR permeation, both transdermally and intradermally following application of a dissolving microarray patch (MAP) to excised neonatal porcine skin. Graphical Abstract

Association of PRLR, IGF1, and LEP genes polymorphism with milk production and litter size in Egyptian Zaraibi goat - Haidan M. El-Shorbagy; Ehab S. Abdel-Aal; Shaimaa A. Mohamed; Akmal A. El-Ghor (Tropical Animal Health and Production, 2022)
Studying variation in genes responsible for physiological characters is important to enhance goat productive and reproductive efficiency. This study aimed to detect specific nucleotide polymorphisms in prolactin receptor (PRLR), insulin-like growth factor (IGF1), and leptin (LEP) genes and their correlation with milk production (MP) and litter size (LS) traits in Zaraibi goat. PCR-SSCP products of different patterns of each gene were sequenced and aligned to reveal two mutations (T > C) and (G > A) in 3′UTR of PRLR gene and registered on NCBI with accession numbers OM418863 for TT and OM418864 for CT, while (G > A) variation was registered as OM418861 for GG and OM418862 for AG in exon 10. TT, CT, AG, and GG genotypes were distributed in the studied animals with frequencies 0.43, 0.57, 0.65, and 0.35, respectively. While alleles C, T, A, and G frequencies were 0.28, 0.72, 0.32, and 0.68, respectively. CT and AG genotypes associated significantly ( P < 0.05) with higher MP and LS, respectively. By studying the haplotypes of PRLR, C-A and T-A were associated with the highest and the lowest level of MP, respectively. For LS, T-A and C-G showed significant correlation with the highest and the lowest rate, respectively. Regarding IGF1 gene, two polymorphisms were detected; T74C at exon 4 which registered on NCBI as OM418860, and combined mutations as ins. G470, A531G, and T534C (PP genotype) at 5′ flanking region that registered as OM418859. For LEP, only one polymorphism was found in intron 2 (G281A) which submitted to NCBI as OM418855. All detected polymorphisms have shown to be involved in regulating the MP or LS as reproductive traits in goat.

Change Detection Analysis using Bitemporal PRISMA Hyperspectral Data: Case Study of Magelang and Boyolali Districts, Central Java Province, Indonesia - Sanjiwana Arjasakusuma; Sandiaga Swahyu Kusuma; Pegi Melati; Akmal Hafiudzan (Journal of the Indian Society of Remote Sensing, 2022)

Identification of novel biofilm genes in avian pathogenic Escherichia coli by Tn5 transposon mutant library - Jiangang Hu; Yi Gu; Huiqi Lu; Muhammad Akmal Raheem; Fangheng Yu; Xiangpeng Niu; Jiakun Zuo; Huifang Yin; Cuiqin Huang; Xiangjun Song; Jian Tu; Wen Zhou; et al. (World Journal of Microbiology and Biotechnology, 2022)

Microneedle-Mediated Permeation Enhancement of Chlorhexidine Digluconate: Mechanistic Insights Through Imaging Mass Spectrometry - Melissa Kirkby; Akmal Bin Sabri; David Scurr; Gary Moss (Pharmaceutical Research, 2022)
Purpose Chlorhexidine digluconate (CHG) is a first-line antiseptic agent typically applied to the skin as a topical solution prior to surgery due to its efficacy and safety profile. However, the physiochemical properties of CHG limits its cutaneous permeation, preventing it from reaching potentially pathogenic bacteria residing within deeper skin layers. Thus, the utility of a solid oscillating microneedle system, Dermapen®, and a CHG-hydroxyethylcellulose (HEC) gel were investigated to improve the intradermal delivery of CHG. Methods Permeation of CHG from the commercial product, Hibiscrub®, and HEC-CHG gels (containing 1% or 4% CHG w/w) was assessed in intact skin, or skin that had been pre-treated with microneedles of different array numbers, using an Franz diffusion cells and Time-of-Flight Secondary Ion Mass Spectrometry (ToF–SIMS). Results Gels containing 1% and 4% CHG resulted in significantly increased depth permeation of CHG compared to Hibiscrub® (4% w/v CHG) when applied to microneedle pre-treated skin, with the effect being more significant with the higher array number. ToF–SIMS analysis indicated that the depth of dermal penetration achieved was sufficient to reach the skin strata that typically harbours pathogenic bacteria, which is currently inaccessible by Hibiscrub®, and showed potential lateral diffusion within the viable epidermis. Conclusions This study indicates that HEC-CHG gels applied to microneedle pre-treated skin may be a viable strategy to improve the permeation CHG into the skin. Such enhanced intradermal delivery may be of significant clinical utility for improved skin antisepsis in those at risk of a skin or soft tissue infection following surgical intervention.

Plastics in the environment as potential threat to life: an overview - Imania Ghaffar; Muhammad Rashid; Muhammad Akmal; Ali Hussain (Environmental Science and Pollution Research, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Vulnerability Status of the Coral Ecosystem in Kepulauan Seribu Marine National Park, Indonesia - Yonvitner; Syamsul Bahri Agus; Dea Fauzia Lestari; Riza Pasaribu; Eko Supriyanto; Cahyo Widodo; Ayub Sugara; Jiří Patoka; Surya Gentha Akmal (Coastal Management, 2022)

Thermal comfort analysis of fired-clay brick, cement-sand block and cement stabilized earth block masonry house models - Navaratnarajah Sathiparan; Daniel N. Subramaniam; K. G. N. Malsara; M. S. M. Akmal (Innovative Infrastructure Solutions, 2022)

Addressing the unfulfilled codex standard for honey for stingless bee honey through lyophilization - Chin-Hong Yong; Syahidah Akmal Muhammad; Widad Fadhullah; Hasnuri Mat Hassan; Ainolsyakira Mohd Rodhi; Mohd Zulkifli Mustafa; Simon D. Kelly (Isotopes in Environmental and Health Studies, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Investigating the nexus among sulfur dioxide emission, energy consumption, and economic growth: empirical evidence from Pakistan - Khuda Bakhsh; Tanzila Akmal; Tauqeer Ahmad; Qasir Abbas (Environmental Science and Pollution Research, 2022)

Hypogene kaolin deposits from felsic intrusive rocks (Peninsular Malaysia) with special reference to rare earth elements and stable isotopes geochemistry - Hassan Baioumy; Mohsen Farahat; Mohd Hariri Arifin; Mohammad Noor Akmal Bin Anuar; Khaled Al-Kahtany (Geosciences Journal, 2021)

Exposure to Lead Nitrate Alters Growth and Haematological Parameters of Milkfish (Chanos chanos) - Ilham Zulfahmi; Alfinatul Rahmi; Muliari Muliari; Yusrizal Akmal; Epa Paujiah; Kizar Ahmed Sumon; Mohammad Mahmudur Rahman (Bulletin of Environmental Contamination and Toxicology, 2021)

Biosorption of chromium from tannery effluent using carbon-activated algae granules of Chlorella vulgaris and Scenedesmus obliquus - S. S. Mirza; M. Eida; F. Jabeen; M. Iqtedar; A. Mahmood; M. Akmal; M. Sabir (International Journal of Environmental Science and Technology, 2021)

Comparison of Early Succession and Scleractinian Recruitment Between Artificial Live Rocks and Terracotta Tiles - Yusof Muhammad Hamizan; Shahbudin Saad; Mohd Azrul Naim; Mohd Fikri Akmal Khodzori; Muhammad Faiz Mohd Hanapiah (Ocean Science Journal, 2021)

The impasse of energy consumption coupling with pollution haven hypothesis and environmental Kuznets curve: a case study of South Asian economies - Shahzada M. Naeem Nawaz; Shahzad Alvi; Tanzila Akmal (Environmental Science and Pollution Research, 2021)

Correction to: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

RETRACTED ARTICLE: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Surgical Drill Bit Design and Thermomechanical Damage in Bone Drilling: A Review - Mohd Faizal Ali Akhbar; Akmal Wani Sulong (Annals of Biomedical Engineering, 2021)

Potential Risk and Occupational Exposure of Pesticides Among Rice Farmers of a Village Located in Northern Peninsular of Malaysia - Nur Anis Ahmad; Ali Salehabadi; Syahidah Akmal Muhammad; Mardiana Idayu Ahmad (Exposure and Health, 2020)

Baseline assessment of coral health and disease in Tioman Island Marine Park, Malaysia - K. Fikri Akmal; Saad Shahbudin (Community Ecology, 2020)

Vulnerability of marine resources to small‐scale fishing in a tropical area: The example of Sunda Strait in Indonesia - Yonvitner Yonvitner; Josep LIoret; Mennofatria Boer; Rahmat Kurnia; Surya Gentha Akmal; Ernik Yuliana; Diarsi Eka Yani; Sílvia Gómez; Ludivica Endang Setijorini (Fisheries Management and Ecology, 2020)
Although small‐scale fisheries (SSF) play an important socio‐economic role in developing nations, overfishing seems to be increasing the risk of stock vulnerability. This study aims to quantify the pressure of SSF on fish stocks in Sunda Strait (Indonesia) using several biological indicators that are important in quantifying fishing pressure. Data on these indicators were collected monthly for three years (2012–2014) in one of the main fishing ports of the area. The results provide evidence that, although SSF would appear to be the most environmentally sustainable of all the fishing techniques being used today in the coastal waters of Indonesia, the impact of SSF fishing on juvenile fishes in certain areas such as the Sunda Strait must not be underestimated. The results also show the need to protect immature fish of species that are not only commercialised but are also important in subsistence fisheries. Although further studies are needed to assess the impact of SSF on fish stocks in the area, it is suggested management recommendations that include the implementation of marine‐protected areas in nursery grounds and establishing minimum landing sizes well above the size‐at‐maturity for each species, are needed.

Toxicity of palm oil mill effluent on the early life stages of Nile tilapia (Oreochromis niloticus, Linnaeus 1758) - Muliari Muliari; Ilham Zulfahmi; Yusrizal Akmal; Ni Wayan Kurniani Karja; Chairun Nisa; Kizar Ahmed Sumon; Mohammad Mahmudur Rahman (Environmental Science and Pollution Research, 2020)

Induction of fetal abnormalities and genotoxicity by molybdenum nanoparticles in pregnant female mice and fetuses - Hanan R.H Mohamed; Radwa H. El-Atawy; Ahmed M. Ghoneim; Akmal A. El-Ghor (Environmental Science and Pollution Research, 2020)

Simulating Crop Productivity in a Triple Rotation in the Semi-arid Area of the Aral Sea Basin - Nazar Ibragimov; Yulduzoy Djumaniyazova; Jamila Khaitbaeva; Shirin Babadjanova; Jumanazar Ruzimov; Akmal Akramkhanov; John Lamers (International Journal of Plant Production, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Estimation of genomic instability and mutation induction by graphene oxide nanoparticles in mice liver and brain tissues - Hanan R. H. Mohamed; Mary Welson; Ahmed Essa Yaseen; Akmal A. EL-Ghor (Environmental Science and Pollution Research, 2020)

Impact of biochar with different organic materials on carbon fractions, aggregate size distribution, and associated polysaccharides and soil moisture retention in an arid soil - Munir Abbas; Shahzada Sohail Ijaz; Muhammad Ansar; Qaiser Hussain; Asma Hassan; Muhammad Akmal; Muhammad Tahir; Muhammad Iqbal; Kashif Bashir; Sana-ur-Rehman (Arabian Journal of Geosciences, 2019)

Diversity and Abundance of Scleractinian Corals in the East Coast of Peninsular Malaysia: A Case Study of Redang and Tioman Islands - Khodzori Fikri Akmal; Saad Shahbudin; Mohd Hanapiah Muhammad Faiz; Yusof Muhammad Hamizan (Ocean Science Journal, 2019)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Carbon mineralization in subtropical dryland soil amended with different biochar sources - Sehar Sultan; Khalid Saifullah Khan; Muhammad Akmal; Zammurad Iqbal Ahmed; Qaiser Hussain; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Identifying a Gene Knockout Strategy Using a Hybrid of Simple Constrained Artificial Bee Colony Algorithm and Flux Balance Analysis to Enhance the Production of Succinate and Lactate in Escherichia Coli - Mei Kie Hon; Mohd Saberi Mohamad; Abdul Hakim Mohamed Salleh; Yee Wen Choon; Kauthar Mohd Daud; Muhammad Akmal Remli; Mohd Arfian Ismail; Sigeru Omatu; Richard O. Sinnott; Juan Manuel Corchado (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Modelling End-of-Season Soil Salinity in Irrigated Agriculture Through Multi-temporal Optical Remote Sensing, Environmental Parameters, and In Situ Information - Murodjon Sultanov; Mirzakhayot Ibrakhimov; Akmal Akramkhanov; Christian Bauer; Christopher Conrad (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2018)

Earthworms as plug flow reactors: a first-order kinetic study on the gut of the vermicomposting earthworm Eudrilus eugeniae - Katheem Kiyasudeen; Mahamad Hakimi Ibrahim; Syahidah Akmal Muhammad; Sultan Ahmed Ismail; Fadzil Noor Gonawan; Mark Harris Zuknik (Environmental Science and Pollution Research, 2018)

Performance of biotic indices in comparison to chemical-based Water Quality Index (WQI) in evaluating the water quality of urban river - Wan Mohd Hafezul Wan Abdul Ghani; Ahmad Abas Kutty; Mohd Akmal Mahazar; Salman Abdo Al-Shami; Suhaila Ab Hamid (Environmental Monitoring and Assessment, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

Concentrations of Cadmium, Copper, and Zinc in Macrobrachium rosenbergii (Giant Freshwater Prawn) from Natural Environment - Farah Akmal Idrus; Masania Mohd Basri; Khairul Adha A. Rahim; Nur Syazwani Abd Rahim; Melissa Dennis Chong (Bulletin of Environmental Contamination and Toxicology, 2018)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

Integrated microfossil biostratigraphy, facies distribution, and depositional sequences of the upper Turonian to Campanian succession in northeast Egypt and Jordan - Sherif Farouk; Fayez Ahmad; John H. Powell; Akmal M. Marzouk (Facies, 2016)

Comparative Analysis of Free Amino Acids and Nitrogen in Cotton Leaves Treated with Different Classes’ Insecticides - Akmal Asrorov; Ildiko Matusikova; Uchkun Ishimov; Jamolitdin Ziyavitdinov; Olga Veshkurova; Shavkat Salikhov (Agricultural Research, 2015)

Bioactive constituents from Croton sparsiflorus Morong - Durre Shahwar; Naeem Ahmad; Asma Yasmeen; Muhammad Akmal Khan; Sami Ullah; Rahman Atta-ur (Natural Product Research, 2015)

The assessment of spatial distribution of soil salinity risk using neural network - Akmal Akramkhanov; Paul L. G. Vlek (Environmental Monitoring and Assessment, 2012)

Generic medicines in Pakistan: a viable cost-effective option for consumers - Shazia Qasim Jamshed; Mohamed Izham Mohamed Ibrahim; Asrul Akmal Shafie; Mohamed Azmi Hassali; Zaheer Babar (European Journal of Clinical Pharmacology, 2011)

Constitutive expression of high-affinity sulfate transporter (HAST) gene in Indian mustard showed enhanced sulfur uptake and assimilation - M. Z. Abdin; M. Akmal; M. Ram; T. Nafis; P. Alam; M. Nadeem; M. A. Khan; A. Ahmad (Protoplasma, 2011)

Enhancement of artemisinin content by constitutive expression of the HMG-CoA reductase gene in high-yielding strain of Artemisia annua L. - Tazyeen Nafis; Mohd. Akmal; Mauji Ram; Pravej Alam; Seema Ahlawat; Anis Mohd; Malik Zainul Abdin (Plant Biotechnology Reports, 2011)

Tectonically driven carbonate ramp evolution at the southern Tethyan shelf: the Lower Eocene succession of the Galala Mountains, Egypt - Stefan Höntzsch; Christian Scheibner; Jochen Kuss; Akmal M. Marzouk; Michael W. Rasser (Facies, 2011)

Firefly distribution and abundance on mangrove vegetation assemblages in Sepetang estuary, Peninsular Malaysia - Wan Faridah Akmal Wan Jusoh; Nor Rasidah Hashim; Zelina Z. Ibrahim (Wetlands Ecology and Management, 2010)

An assessment of the potential and impacts of winter water banking in the Sokh aquifer, Central Asia - Inna Gracheva; Akmal Karimov; Hugh Turral; F. Miryusupov (Hydrogeology Journal, 2009)

A simple method for simultaneous determination of some organic liquids in in-process materials and effluents produced in the manufacture of amoxicillin and ampicillin - Mohammad S Iqbal; Muhammad A Akmal (Environmental Monitoring and Assessment, 2009)

Influence of various diet regimens on deterioration of hepatic function and hematological parameters following carbon tetrachloride: a potential protective role of natural honey - Noori S. Al-Waili; Khelod Y. Saloom; Thia N. Al-Waili; Ali N. Al-Waili; Mohammad Akmal; Faiza S. Al-Waili; Hamza N. Al-Waili (Natural Product Research, 2006)

Platform configuration, microfacies and cyclicities of the upper Albian to Turonian of west-central Jordan - Frauke Schulze; Jochen Kuss; Akmal Marzouk (Facies, 2005)

Growth responses of seminal roots of wheat seedlings to a reduction in the water potential of vermiculite - Mohammad Akmal; Tadashi Hirasawa (Plant and Soil, 2004)